2015
DOI: 10.1002/cem.2769
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐interaction relationship study of N‐(4‐phenylsubstituted) cyanoacetamides by multivariate methods

Abstract: Derivatives of amides belong to a very attractive group of compounds due to a broad spectrum of different biological activities. The type of molecule activity significantly depends on its interactions with the environment, which on the other hand largely depends on the nature of the substituent attached to the basic molecule as well as of solvents properties. In this work, the influence of the mentioned parameters on the interaction ability of the group of N-(4-phenylsubstituted) cyanoacetamides is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In contrast to the classical linear regression, multivariate methods can give a more comprehensive insight into the dependencies that exist among the analyzed data . In order to establish a model that defines a qualitative and/or quantitative relationship between the chemical structure and the studied properties of molecules, as well as the relationship between the studied parameters of potential biological activity, all the obtained results, R M 0 , m , determined in both modifiers and both stationary phases, including the standard parameter of lipophilicity, pharmacokinetic predictors, and toxicity parameters, were analyzed using cluster analysis (CA) and principal component analysis (PCA).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the classical linear regression, multivariate methods can give a more comprehensive insight into the dependencies that exist among the analyzed data . In order to establish a model that defines a qualitative and/or quantitative relationship between the chemical structure and the studied properties of molecules, as well as the relationship between the studied parameters of potential biological activity, all the obtained results, R M 0 , m , determined in both modifiers and both stationary phases, including the standard parameter of lipophilicity, pharmacokinetic predictors, and toxicity parameters, were analyzed using cluster analysis (CA) and principal component analysis (PCA).…”
Section: Resultsmentioning
confidence: 99%
“…A SAR study involving thiochroman-4-one derivatives found that compounds containing 1,1-dioxo-2-aryl-4H-thiochromen-4-one scaffolds displayed good antileishmanial activity below 10 µM. Ester and amide derivatives of thiochroman-4-ones were also include in this study; the amides tend to form intermolecular and intramolecular hydrogen bonds with other groups [11] and esters are used for masking polar moieties and taking advantage of the availability of endogenous, non-specific esterases, release the molecule inside the cell [12].…”
Section: Introductionmentioning
confidence: 98%
“…Multivariate analysis and the principal component analysis (PCA) in particular are becoming increasingly popular in processing this type of data 12–14 . As its main characteristic, PCA has the ability to recognize and eliminate redundant data, thereby achieving a significant reduction in the number of analyzed data with minimal loss of essential information 15,16 . Therefore, its application significantly facilitates the understanding of the connection between a large number of analyzed data of different origins.…”
Section: Introductionmentioning
confidence: 99%